Growing a glue factory: Open questions in laticifer development. (December 2021) - Johnson, Arielle R.; Moghe, Gaurav D.; Frank, Margaret H.
Abstract: Latex-containing cells called laticifers are present in at least 41 flowering plant families and are thought to have convergently evolved at least 12 times. These cells are known to function in defense, but little is known about the molecular genetic mechanisms of their development. The expansion of laticifers into their distinctive tube shape can occur through two distinct mechanisms, cell fusion and intrusive growth. The mechanism and extent of intrusive laticifer growth are still being investigated. Hormonal regulation by jasmonic acid and ethylene is important for both laticifer differentiation and latex biosynthesis. Current evidence suggests that laticifers can be specified independently of latex production, but extensive latex production requires specified laticifers. Laticifers are an emerging system for studying the intersection of cell identity specification and specialized metabolism.